Youth Health Trends in Northern Portugal: Analyzing Diet, Physical Activity, and Body Image - Maria Teresa Moreira; Sandra Rodrigues; Andreia Lima; Salomé Ferreira; Carla Sílvia Fernandes; Clarinda Festas (Youth)
(1) Background: In the face of global concerns regarding unhealthy lifestyles among youths, understanding dietary habits, physical activity, and weight management strategies among third-cycle students in Portugal becomes essential. This study aims to evaluate the extent to which middle school students adhere to the Mediterranean diet and assess their physical activity habits and overall weight perceptions. (2) Methods: This study is a cross-sectional observational study. Using self-reported data from a sample of 232 students aged between 12 and 18, this study delved into their dietary patterns, engagement in physical activities, perceptions of weight, and weight management approaches, measured by the KIDMED and YRB questionnaires. (3) The results demonstrated that adolescents engaged in a varied diet, and 65.5% had recently engaged in physical activity. However, 25% reported exercise-related injuries, suggesting potential safety gaps. Extreme weight management practices were minimal, but a disparity in weight perception and weight loss desire emerged, hinting at underlying societal and media influences. Gender differences in certain habits were minimal. (4) Conclusions: While students were generally inclined towards healthy habits, there are evident areas of concern, particularly regarding safety in physical activities and weight perceptions. In the future, interventions should be implemented to increase students’ literacy and raise awareness of the Mediterranean diet and physical well-being.